Immune modulation via T regulatory cell enhancement: Disease‐modifying therapies for autoimmunity and their potential for chronic allergic and inflammatory diseases—An EAACI position paper of the Task Force on Immunopharmacology (TIPCO). Issue 1 (7th January 2021) - Roth‐Walter, Franziska; Adcock, Ian M.; Benito‐Villalvilla, Cristina; Bianchini, Rodolfo; Bjermer, Leif; Boyman, Onur; Caramori, Gaetano; Cari, Luigi; Fan Chung, Kian; Diamant, Zuzana; Eguiluz‐Gracia, Ibon; Knol, Edward F.; et al.
Abstract: Therapeutic advances using targeted biologicals and small‐molecule drugs have achieved significant success in the treatment of chronic allergic, autoimmune, and inflammatory diseases particularly for some patients with severe, treatment‐resistant forms. This has been aided by improved identification of disease phenotypes. Despite these achievements, not all severe forms of chronic inflammatory and autoimmune diseases are successfully targeted, and current treatment options, besides allergen immunotherapy for selected allergic diseases, fail to change the disease course. T cell–based therapies aim to cure diseases through the selective induction of appropriate immune responses following the delivery of engineered, specific cytotoxic, or regulatory T cells (Tregs). Adoptive cell therapies (ACT) with genetically engineered T cells have revolutionized the oncology field, bringing curative treatment for leukemia and lymphoma, while therapies exploiting the suppressive functions of Tregs have been developed in nononcological settings, such as in transplantation and autoimmune diseases. ACT with Tregs are also being considered in nononcological settings such as cardiovascular disease, obesity, and chronic inflammatory disorders. After describing the general features of T cell–based approaches and current applications in autoimmune diseases, this position paper reviews the experimental models testing or supporting T cell–based approaches, especially Treg‐based approaches, in severe IgE‐mediated responses and chronic respiratory airway diseases, such as severe asthma and COPD. Along with an assessment of challenges and unmet needs facing the application of ACT in these settings, this article underscores the potential of ACT to offer curative options for patients with severe or treatment‐resistant forms of these immune‐driven disorders.